The physiological and pharmaceutical roles of MCTs and other ingredients in intravenous emulsions containing omega-3 enriched fish oil designed to mitigate cytokine release syndrome - Driscoll, David F.; Bistrian, Bruce R. (Frontiers in Pharmacology, 2025)
Cytokine release syndrome (CRS) is a serious adverse effect often seen following the administration of cancer immunotherapy, particularly with chimeric antigen receptor (CAR) T cell therapy. Recently, we proposed the administration of precise amounts of the primary active ingredients found in fish oil (EPA + DHA) in combination with medium chain triglycerides (MCTs). Although there is a commercial injectable emulsion containing a refined-only fish oil, it is indicated as a nutritional supplement because it contains highly variable concentrations of the primary active ingredients (±50% of EPA + DHA). We suggested the application of a refined and enriched fish oil in order to provide the desired pharmacological doses according to the typical limits for drugs, i.e., EPA + DHA, within ±10% of the labeled amount. This tight tolerance is not achievable with “refined-only” fish oil indicated for nutrition support. The purpose of this review is to further describe the details of such a dosage form, with particular focus on other active ingredients in the proposed formulation. They play important roles in delivering a safe final product with multiple therapeutic targets for the acute systemic inflammatory response from CRS, as well as addressing chronic inflammation within the tumor microenvironment (TME).